2007
DOI: 10.1093/ajcn/85.4.1031
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fluid skim milk promotes greater muscle protein accretion after resistance exercise than does consumption of an isonitrogenous and isoenergetic soy-protein beverage

Abstract: Milk-based proteins promote muscle protein accretion to a greater extent than do soy-based proteins when consumed after resistance exercise. The consumption of either milk or soy protein with resistance training promotes muscle mass maintenance and gains, but chronic consumption of milk proteins after resistance exercise likely supports a more rapid lean mass accrual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
421
3
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(455 citation statements)
references
References 28 publications
22
421
3
9
Order By: Relevance
“…A consistent finding has been that post-workout protein consumption promotes increments and MPS (9,11,12) , which ultimately sum up to yield muscle hypertrophy. The rise in MPS occurs rapidly following a maximally stimulatory bolus dose of protein (24) being apparent within the first hour after resistance exercise and peaking at 3 h postexercise (9) .…”
Section: Protein Enhances Exercise-induced Rises In Muscle Protein Symentioning
confidence: 61%
See 1 more Smart Citation
“…A consistent finding has been that post-workout protein consumption promotes increments and MPS (9,11,12) , which ultimately sum up to yield muscle hypertrophy. The rise in MPS occurs rapidly following a maximally stimulatory bolus dose of protein (24) being apparent within the first hour after resistance exercise and peaking at 3 h postexercise (9) .…”
Section: Protein Enhances Exercise-induced Rises In Muscle Protein Symentioning
confidence: 61%
“…Empirical support for this thesis has been observed. For example, Wilkinson et al (12) showed a greater acute post-exercise accumulation of muscle protein with milk v. matched soya protein consumption. This acute finding when practised chronically during a 12-week training study resulted in net greater gains in muscle fibre hypertrophy and whole-body lean mass (13) .…”
Section: Protein Enhances Exercise-induced Rises In Muscle Protein Symentioning
confidence: 99%
“…In the present study, we provided milk proteins as the source of dietary nitrogen in the postexercise beverages given that they are complete, high-quality proteins that are generally associated with greater muscle remodeling and recovery after exercise in adults (32). For example, studies in adults have revealed that milk and associated dairy-based proteins (especially whey) support greater rates of muscle protein synthesis and net protein balance after exercise compared with plantbased proteins such as soy (38,46), which can ultimately translate into greater training-induced gains in muscle and lean body mass (20,44). The greater anabolic effect of dairy compared with soy protein in adults occurs despite these sources having similarly high [albeit artificially truncated (37)] protein quality ratings according to the protein digestibilitycorrected amino acid score (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, when comparing the effects of soy with milk, some authors have found that animal protein is better 37,38 . Therefore, the different benefits or effects between animal and vegetable proteins on muscle function recovery should be investigated to better understand whether the tested vegetable protein (pea protein concentrate) could generate the same results as whey protein, since this is the most common protein source added to CHO supplements 1,10,11,14,[18][19][20]22 .…”
Section: Discussionmentioning
confidence: 99%